Krooniliste haiguste ja hulgihaigestumise levimus Eestis: rahvastikupõhine läbilõikeuuring - Jürisson, Mikk; Pisarev, Heti; Uusküla, Anneli; Lang, Katrin; Oona, Marje; Kalda, Ruth (Eesti Arst, 2022)
Eesti Arst 2022; 101(4):249